Poverty in Ukraine due to Russian military aggression - Cherevko, Heorhiy (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
The purpose of this study was to establish the real level of poverty in Ukraine and to determine its meaning and factors of its formation in the specific conditions of Russian military aggression in the country and to form a vision of the nearest prospects of its dynamics. The methodology of the conducted research was formed on the basis of a dialectical approach to the study of socioeconomic phenomena in an organic combination with the methods of analysis and synthesis as well as induction and deduction using the method of scientific abstraction and the analytical-descriptive method. The tool for determining the prevalence of poverty and the degree of impoverishment of the population is the poverty line. Two main methods of its definition are used: normative and relative (statistical). It has been established that the war has caused catastrophic damage to the country’s economy and is the main factor in the sharp increase in the poverty level of the population. At the same time, the issue of poverty is not a priority for the population of Ukraine at present. Purely objectively, for a country under the blows of an aggressor who is waging war to destroy it, the poverty rate makes no economic sense; rather, it has political and social significance. The first task is to end the war in an unambiguous version – the absolute victory of Ukraine, which corresponds to the interests of all civilised humanity. The prospects for reducing the level of poverty in Ukraine depend on the duration of the war and the level of destruction of the country’s economy, as well as the quality of development of the country’s economy and its population at a new level. The latter will depend on the degree of inclusiveness of the new economic and political institutions. It is clear that a purely objective condition for the successful operation of the mentioned factors is the economic and political support of Ukraine by partner countries.

Celem niniejszego badania było ustalenie rzeczywistego poziomu ubóstwa na Ukrainie oraz określenie czynników jego kształtowania się w specyficznych warunkach rosyjskiej agresji militarnej na ten kraj oraz sformułowanie wizji najbliższych perspektyw jego dynamiki. Metodyka prowadzonych badań powstała w oparciu o dialektyczne podejście do badania zjawisk społeczno-ekonomicznych w organicznym połączeniu z metodami analizy i syntezy oraz indukcji i dedukcji z wykorzystaniem metody abstrakcji naukowej oraz metody analityczno-opisowej. Narzędziem służącym do określenia rozpowszechnienia ubóstwa i stopnia zubożenia ludności jest granica ubóstwa. Stosowane są dwie główne metody jego definiowania: normatywna i względna (statystyczna). Ustalono, że wojna wyrządziła katastrofalne szkody w gospodarce kraju i jest głównym czynnikiem gwałtownego wzrostu poziomu ubóstwa ludności. Jednocześnie problem ubóstwa nie jest na razie priorytetem dla ludności Ukrainy. Czysto obiektywnie, dla kraju, znajdującego się pod wpływem agresora, który prowadzi wojnę, aby go zniszczyć, wskaźnik ubóstwa nie ma sensu ekonomicznego, ale ma znaczenie raczej polityczne i społeczne. Najważniejszym zadaniem jest zakończenie wojny w wersji jednoznacznej – absolutnym zwycięstwem Ukrainy, co odpowiada interesom całej cywilizowanej ludzkości. Perspektywy zmniejszenia poziomu ubóstwa na Ukrainie zależą od czasu trwania wojny i stopnia zniszczenia gospodarki kraju, od poziomu jakości rozwoju gospodarki kraju i jego ludności na nowym poziomie. To ostatnie będzie zależeć od stopnia inkluzywności nowych instytucji gospodarczych i politycznych. Jest oczywiste, że czysto obiektywnym warunkiem pomyślnego działania wymienionych czynników jest wsparcie gospodarcze i polityczne Ukrainy przez kraje partnerskie.
Ubóstwo ludności Ukrainy w wyniku rosyjskiej agresji militarnej
Keywords: Ukraine; poverty; welfare; victory; war; wojna; Ukraina; ubóstwo; dobrobyt; zwycięstwo